Assessment of Sediment Quality of Some Heavy Metals in the Con Lu Bay Area, Giao Thuy District, Nam Dinh Province - Thanh, Dinh Xuan; Thuy Duong, Nguyen; Van Huong, Nguyen; Dinh Thai, Nguyen; Thi Dung, Tran; Hong Quan, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 4DO - 10.25073/2588-1094/vnuees.5143, 2024)
Abstract: Surface sediments were sampled in the Con Lu bay area to assess the levels of elemental enrichment, pollution, and ecological risks based on sediment grain sizes and heavy metal concentrations. Our results show that sediments in the bay-mouth area contain coarser and better sorting grain sizes than those in the center of the bay. The mean concentrations of heavy metals were ordered from the highest to the lowest as follows: Zn > Pb > Cu > As > Cd. The levels of geo-accumulation of metals, estimated using the reference background of the global average shale, are low for As, Cd, Cu, Zn, but are moderate to strong for Pb. The average values of metal enrichment factor (EF) are greater than 1.5, indicating the probable influence of anthropogenic activities. The contents of almost all heavy metals (i.e., As, Cd, Cu, Zn) in the sediment samples are lower than their regulation thresholds in the QCVN 43:2017/BTNMT, but Pb concentrations of samples in the bay mouth are ~ 6.5% higher than its regulation threshold. However, the assessment indexes including metal enrichment factor (EF), pollution load index (PLI), and potential ecological risk index (PER) are moderate, implying a sign of pollution and low ecological risk for surface sediments. Therefore, there is a need of early planning to limit the emission of heavy metals in the Con Lu Bay, where aquaculture activities and fishing boats have been concentrated.